Pelatihan Modifikasi Kukis Sagu di Kampung Gwinjaya, Bonggo Timur Sarmi, Provinsi Papua - Suyono, Ign. Joko; Gunaedi, Tri; Busup, Ronald (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
This community service activity aims to improve the quality and quantity of sago cookie products in a modified form from its first form in the village-owned business unit